Penetapan Kadar Flavonoid Total dari Tingkatan Fraksi Ekstrak Daun Sirih Merah Metode Spektrofotometri UV-Vis - Bella Natilla; Rohama; Yusuf Anggro Mukti (Bulletin of Community Engagement, 2024)
Red betel leaf (Piper crocatum Ruiz & Pav) is a plant that grows widely in the Puruk Cahu area of Central Kalimantan and is empirically used as an antiseptic to treat wounds. Red betel leaves contain flavonoid compounds that have antiseptic activity.   Objective: To determine the total flavonoid content at the fraction level of red betel leaf extract using the UV-Vis Spectrophotometry method.  Methods: Experimental method by looking at qualitative data results through color reaction tests and quantitative data to see the effect of total flavonoid levels using UV-Vis Spectrophotometry.  Results: Qualitative analysis of flavonoid compounds using a color reaction test showed positive results containing flavonoids. Quantitative analysis using UV-Vis Spectrophotometry showed that the total flavonoid content of the n-Hexane fraction, ethyl acetate fraction and distilled water fraction was 38 mg QE/g or 3.8%; 42.8 mg QE/g or 4.28%; and 25.6 mg QE/g or 2.56%. The highest total flavonoid levels were found in the ethyl acetate fraction. The results of the One Way Annova test obtained a significance value of 0.000 (p<0.05).  Conclusion: Red betel leaf extract at fraction levels contains flavonoid compounds with total flavonoid levels in the n-Hexane fraction, ethyl acetate fraction and distilled water fraction respectively 38 mg QE/g or 3.8%; 42.8 mg QE/g or 4.28%; and 25.6 mg QE/g or 2.56%, so it was concluded that there was a significant influence of total flavonoid levels on the fraction level of red betel leaf extract using UV-Vis spectrophotometry.